The hedgewitch of Foxhall (HarperTeen, Harperteen, 2024)
"Magic is fading from Wales -- choked off by King Offa's Dyke, the enemy earthworks that spans the entire border. Even the dragons have disappeared. And now an attack is imminent. Prince Taliesin would love to watch magic die. Prince Dafydd fears it, and the throne. But when their father promises the crown to whichever son can destroy the dyke and restore magic to Wales, the brothers are forced into an uneasy rivalry. Ffion works hedgewitch magic for poor folk, not princes. Unlike the power-hungry Foxhall coven, she uses only what nature can spare. But when the coven's greed costs Ffion everything, she will need power beyond her wildest dreams to get back what she's lost."--

The blood years (Balzer + Bray, Balzer + Bray, an imprint of HarperCollinsPublishers, 2023)
"Based on the true experiences of her grandmother's childhood in Holocaust-era Romania, ... author Elana K. Arnold weaves [a] tale of love and loss in the darkest days of the twentieth century--and one young woman's will to survive them"--Publisher description.

Kin: rooted in hope (Atheneum Books for Young Readers, 2023)
"A multi-generational family history told in the voices of the author's ancestors, spanning enslavement alongside Frederick Douglass at Maryland's Wye House plantation, service in the U.S. Colored Troops, andthe founding of all-Black Reconstruction-era communities."--|cProvided by publisher.

Cruel magic: a Victorian faerie tale (Rowan Ridge Press, 2022)
Ball Gowns. Calling Cards. Hell Hounds. Cassandra Weaver is hiding an infirmity from a society--and a family--that demands perfection. Henry Stewart is hiding from his former Faerie masters, trying to remember what it means to be human. Simple enough, except that their little town of Drixton conceals a secret as old as the church bells. The Queen of the Unseelie Fay is hunting a mortal soul there, and Cassandra and Henry stand in her way. They'll need allies to stop her, but whom can they trust? The shape-shifting Fay with his own plans? The social pariah wielding uncanny abilities? The mysterious American who carries silver bullets? The beautiful lady with a dark past? They must decide what--or who--they're willing to sacrifice to defeat the Unseelie Queen because if they fail, the dark magic of the Unseelie Fay will overpower both the mortal and Faerie worlds. Cruel Magic is an action-packed gaslamp fantasy set in a Victorian England rife with secrets, romance, and Faerie enchantments. -- Amazon.com

Ruthless vows: a novel (Letters of enchantment, 2,, 2023)
Two weeks after returning home from the front, Iris and Attie seize another chance to report on Dacre's movements, while Roman, who's lost his memory and is stuck in Dacre's realm, becomes entangled in a mysterious pen pal correspondence, leading to a pivotal decision that could impact the course of the war and his relationship with Iris.

Only this beautiful moment (Balzer + Bray, Balzer + Bray, an imprint of HarperCollinsPublishers, 2023)
"2019. Moud is an out gay teen living in Los Angeles with his distant father, Saeed. When Moud gets the news that his grandfather in Iran is dying, he accompanies his dad to Tehran, where the revelation of family secrets will force Moud into a new understanding of his history, his culture, and himself. 1978. Saeed is an engineering student with a promising future ahead of him in Tehran. But when his parents discover his involvement in the country's burgeoning revolution, they send him to safety in America, a country Saeed despises. And even worse--he's forced to live with the American grandmother he never knew existed. 1939. Bobby, the son of a calculating Hollywood stage mother, lands a coveted MGM studio contract. But the fairy-tale world of glamour he's thrust into has a dark side. Set against the backdrop of Tehran and Los Angeles, this tale of intergenerational trauma and love is an ode to the fragile bonds of family, the hidden secrets of history, and all the beautiful moments that make us who we are today"--

A fragile enchantment (St. Martin's Publishing Group, Macmillan Audio, Wednesday Books, 2024)
"When eighteen-year-old magical dressmaker Niamh is commissioned for a royal wedding, she finds herself embroiled in scandal when a gossip columnist draws attention to her undeniable chemistry with the groom."--